Management of the company's innovation activities - Qin Hao (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
he object of research is the company Mei Tuan. The subject of research is the management of the company’s innovation activities, focusing on strategies and practices for sustainable development. The purpose of the master's thesis is to develop scientific and practical recommendations for enhancing Mei Tuan’s innovation management system to improve operational efficiency, foster long-term competitiveness, and support sustainable development initiatives. The research outcomes contribute to the theoretical understanding of innovation management and provide practical principles for improving corporate innovation systems. The recommendations proposed in the thesis include actionable strategies for Mei Tuan to optimize its innovation processes, integrate sustainable practices, and strengthen its market position. The obtained results have practical implications that extend beyond Mei Tuan, offering valuable insights for other companies seeking to enhance their innovation activities in the digital economy while adhering to principles of sustainable development. These findings are particularly relevant in the context of rapid technological advancement and increasing global emphasis on sustainability.
Scientific advisor: Morozova N., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; innovation; innovation activities; strategic approach; company's innovation potential; technologies in innovation management